Rationality, Impossibility, and Analogy: Gadamer's Hermeneutics and the "Theological" Turn in French Phenomenology - Della Zazzera, Anthony (Université d'Ottawa / University of Ottawa, 2020)
In contemporary, French phenomenology, a debate has arisen concerning whether phenomenology can allow for a certain kind of “theological” consideration. In particular, Jean-Luc Marion argues that the potential of the reduction has not been fully explored and that a full reduction to pure givenness in fact allows one to give an account of the paradoxical experience of the impossible beyond experience, which is described as a phenomenon of revelation and may include a Revelation of God. Marion’s claims have been considered contentious. As I interpret it, the debate plays out between 1) those who also admit that phenomenology can occasion a form of “theological” consideration, but maintain, unlike Marion, that it remains a more existential affirmation of the impossible beyond experience, represented by Jacques Derrida and John Caputo, and 2) those who refuse any role for this impossible beyond experience within phenomenology (and perhaps more generally), and insist that phenomenology be preserved as an essentialist science of the appearances, represented by Dominique Janicaud. I take the positions of Derrida and Caputo, on the one hand, and Janicaud, on the other, to each entail extreme consequences that ought to be avoided—the former resulting in a form of irrationalism and the latter converting phenomenology into a form of pragmatism. Furthermore, I find Marion’s basic claim, that the impossible beyond experience ought to have a role in shaping finite experience, to be worth investigating further. However, Marion concedes too much to the deconstructive position of Derrida and Caputo at the outset, and so I find that the philosophy of Hans-Georg Gadamer provides an opportunity to correct some of the deficiencies in Marion’s position, but also argue to a similar end as he does. I find that Gadamer’s position incorporates an implicit analogical structure between rational experience and the impossible, thereby permitting one to maintain the impossible as impossible, but also affirm a certain possibility for understanding it.
Keywords: Philosophy; Phenomenology; Hermeneutics; Theology; Deconstruction; Analogy; Impossibility; Rationality; Hans-Georg Gadamer; Jean-Luc Marion; Jacques Derrida; Dominique Janicaud; John D. Caputo